(untitled) (Cadernos ESP, 2023)
To characterize the scientific production about the perception of nursing professionals regarding care for HIV/AIDS carriers. This is an integrative review of the literature on the perception of nursing professionals regarding care for HIV/AIDS patients. In relation to the years 2013 and 2016, there was a greater number of publications on the subject, with 37.5% each. In the years 2011 and 2017, there was a lower number of publications, with a value of 12.5% ​​each, and through the research carried out in the VHL, it was noticed that the Revista Brasileira de Enfermagem had a greater number of publications, with 37.5%. It was possible to observe the knowledge about the nursing problems that make their care difficult, and the importance of a more centered and human view in the care aimed at seropositive patients.